Pengaruh Kreativitas Guru Dan Fasilitas Pembelajaran Terhadap Hasil Belajar Materi Bangun Datar Kelas IV SD - Saputro, Hengkang Bara; Rorenza, Nila (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2024)
The purpose of this study was to describe the effect of teacher creativity and learning facilities on student learning outcomes in flat shape materials at SD MBS Prambanan. The population in this study were fourth grade elementary school students, totaling 45 people. The sample in this study were all fourth grade students consisting of one class whose sample consisted of 45 students with a total of 23 girls and 22 boys. In this study, the independent variables were the creativity of the teacher (x₁) and learning facilities for flat shapes (x₂) while the dependent variable was the result of learning mathematics (Y). Data collection techniques using questionnaires with validity and reliability tests; and documentation. The research results show thatthere is a difference in student learning outcomes in class IV math subject matter between teacher creativity and learning facilities, namely the sig (2 tailed) value of 0.002 <0.05 which means the working hypothesis (Ha) in this study is accepted, while the null hypothesis (H0) rejected. Thus it is known that there is an influence between teacher creativity and learning facilities on student learning outcomes in flat shape material for class IV mathematics at SD MBS Prambanan.